Sustainable Purchases: Benefits and Obstacles in a Community College - Ferreira, Denise Helena Lombardo; Sugahara, Cibele Roberta; Jacob, Antonio Aparecido (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
The practice of sustainable purchasing is relevant for addressing environmental, economic, and social dimensions. However, this practice occurs frequently in public companies due to legal requirements of Public Procurement Law. Private Community Colleges, on the other hand, are not subject to these requirements. In this context, the objective of this research is to identify the benefits and obstacles of adopting sustainable purchasing practices in a Private Community College. The research methodology is exploratory, and the data collection procedure is documental. As a result, the possibility of adopting key sustainable purchasing practices is discussed, presenting the obstacles and benefits of sustainable purchases in a Higher Education Institution (HEI), with a focus on addressing social, economic, and environmental dimensions, aiming to explore possibilities for implementing these practices. In the final considerations, the advantages of adopting sustainable purchases by HEIs are argued, emphasizing the importance of taking a stance to promote initiatives that encourage more sustainable consumption patterns, as universities play a crucial role in the social and professional development of individuals.